Academic writing: on the way to interdisciplinary unity - I. В. Korotkina (Высшее образование в России)
The author reviews the previously published articles on academic writing concerning the key terms. She refers to the western system of developing academic skills and academic literacy in an attempt to prevent misunderstandings among specialists in different disciplines.